Meningkatkan Hasil Belajar Pendidikan Agama Islam Menggunakan Metode Tutor Sebaya - Indah Novianti Suhara Komar; Fitroh Hayati; Huriah Rachmah (Bandung Conference Series: Islamic Education, 2023)
Abstract. Education according to its path consists of: formal, informal and non-formal education. Nonformal education (PNF) pathways include life skills education, PAUD, youth education, women's empowerment education, literacy education, family education, skills education and job training/ courses, equality education pursue packages, and other education aimed at developing the abilities of learners. This research study is based on the situation of learners (learning citizens) in equality education institutions that come from various circles. Because of this, PKBM (Community Learning Activity Center) Holis Bandung has its own innovation by applying peer tutor methods in learning so that the results of learning that have been done can increase. This research aims to find out the planning, implementation and evaluation of PAI (Islamic Religious Education) learning using peer tutor methods in improving learners' learning outcomes at PKBM Holis Bandung City. The type of approach used in this study is a qualitative approach with case study methods. Data collection techniques through interviews, observations and documentation studies. Based on the results of data processing, the planning carried out in using peer tutor methods for PAI learning is to prepare RPP (Learning Implementation Plan), lesson schedule, peer tutor method learning planning, media used. While the implementation of PAI learning carried out by peer tutor methods is carried out neatly and neatly, the implementation using the peer tutor method consists of preliminary activities, core activities, closing activities. These activities have been carried out well in accordance with the main purpose of learning using peer tutor methods, namely improving learning outcomes. And for the evaluation carried out, the core tutor provides an assessment based on several aspects, namely the family aspect, the skills aspect, the cognitive aspect. Abstrak. Pendidikan menurut jalurnya terdiri atas: pendidikan formal, informal dan nonformal. Jalur pendidikan nonformal (PNF) meliputi pendidikan kecakapan hidup, PAUD, pendidikan kepemudaan, pendidikan pemberdayaan perempuan, pendidikan keaksaraan, pendidikan keluarga, pendidikan keterampilan dan pelatihan kerja/ kursus, pendidikan kesetaraan kejar paket, serta pendidikan lain yang ditujukan untuk mengembangkan kemampuan peserta didik. Jenis pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif dengan metode studi kasus. Adapun teknik pengumpulan data melalui wawancara, observasi dan studi dokumentasi. Berdasarkan hasil pengolahan data, perencanaan yang dilakukan dalam menggunakan metode tutor sebaya untuk pembelajaran PAI adalah dengan menyiapkan RPP (Rencana Pelaksanaan Pembelajaran), jadwal pelajaran, perencanaan pembelajaran metode tutor sebaya, media yang digunakan. Sedangkan Pelaksanaan pembelajaran PAI yang dilaksanakan dengan metode tutor sebaya terlaksana dengan tersusun dan rapi, pelaksanaan menggunakan metode tutor sebaya terdiri atas kegiatan pendahuluan, kegiatan inti, kegiatan penutup. Kegiatan tersebut telah terlaksana dengan baik sesuai tujuan utama pembelajaran menggunakan metode tutor sebaya yaitu meningkatkan hasil belajar. Dan untuk evaluasi yang dilakukan, tutor inti memberikan penilaian berdasar pada beberapa aspek, ialah aspek kekeluargaan, aspek keterampilan, aspek kognitif.